Effect of Ultrasound Treatment on Allergenicity Reduction of Milk Casein via Colloid Formation - Wang, Chong; Xie, Qiang; Wang, Yanbo; Fu, Linglin (Journal of agricultural and food chemistry, 2020)
Cow's milk protein allergy, which occurs in approximately 5-10% of the population of infants and children, has become an important public food safety problem. As a major allergen in cow's milk, the most abundant protein casein (CN) is considered to be potent in inducing food allergy. In recent years, ultrasound treatment has played a significant role in the field of colloidal particulate system. In this study, we found that ultrasound treatment dramatically decreased the diameter of a CN particle to less than 100 nm in the presence of Tween 80, producing colloidal casein (c-CN) with high transparency. The electrophoretic and transmission electron microscopy analysis showed that the advanced protein structure of CN changed significantly. In addition, the enzyme-linked immunosorbent assay with allergic sera showed that the immunoglobulin-E-binding capacity of c-CN was significantly decreased. In the meantime, the LAD2 mast cell line degranulation assay demonstrated that ultrasound treatment made CN hypoallergenic. The colloidal and hypoallergenic properties of c-CN were stably maintained for more than 30 days. Likewise, the allergenicity of fresh whole milk also decreased after ultrasound treatment. This work provided an effective way to reduce the allergenicity of milk allergen, which could be beneficial to the production of hypoallergenic cow's milk.